Does Gender Modify the Effects of Race–ethnicity on Criminal Sanctioning? Sentences for Male and Female White, Black, and Hispanic Defendants - Steffensmeier, Darrell J. (Journal of quantitative criminology, 2006)
Using data from large urban courts for the years 1990–1996 and drawing from the “focal concerns” framework on case-process decision making, we examine the main and interactive effects of gender and race–ethnicity on sentence outcomes. The main focus of the present study is whether the effects of race–ethnicity (and gender) on sentence outcomes are similar or different across gender (and racial–ethnic) groups. Consistent with the findings of prior research, we find that female defendants receive more lenient sentences than male defendants and that black and Hispanic defendants receive less favorable treatment than white defendants. However, these main effects are strongly dependent on whether the sample is partitioned by gender or race–ethnicity. We find that race–ethnicity influences male but not female sentences. Conversely, gender strongly influences sentencing across all racial–ethnic groups. These findings are at odds with the traditional view that leniency in court sanctioning typically by-passes “women of color.” Instead, it appears that black and Hispanic female defendants actually benefit more from their “female” status than would be expected all else equal.